Multiple valuation method: difference between market price & implied share price of USA’s machinery – construction & mining Industry - Shariar, Sajid (Brac University, 2022)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2021.